Influence of Microscopic Particle Flow on Thermal Elastohydrodynamic Lubrication of Spur Gear - Huang Xingbao; Wang Youqiang; Liu Qian; Dong Ning (Jixie chuandong)
The powder particles flow lubrication mathematical model is established. The thermal elastohydrodynamic lubrication of spur gears are investigated with considering quantitative influence of particles flow on oil rheological viscosity and density,reckoning in time-varying effect and thermal effect. The influence of different mass fraction of MoS2 on film pressure,film thickness and temperature are analyzed. The influences of synthetic diamond,45 steel,graphite and MoS2 with 5% mass fraction on film pressure,film thickness and temperature are compared. Finally,the comparative validation is carried out according to the existing experimental results. Results show that the noticeable increase in mass fraction of MoS2 may cause a slight reduction in the maximum temperature,a remarkable reduction in the minimum film thickness and a distinct reduction in contact centre transient temperature at pitch point. The graphite and MoS2 particles flow with low friction coefficient and low hardness have preferable lubrication effects. However,the synthetic diamond and 45 steel particles flow with high friction coefficient and high hardness are harmful to lubrication.